Plasma simulation of complex HL‐2M divertor geometries using SOLEDGE2D‐EIRENE edge plasma transport code. Issue 6 (14th February 2018) - Mao, R.; Fedorczak, N.; Ciraolo, G.; Bufferand, H.; Zheng, G.Y.; Li, J.X.
Abstract : In this paper, we present the initial results of a fundamental study of the impact of the magnetic configuration on the detachment behaviour and heat exhaust in HL‐2M simulation for low power. Starting from typical HL‐2M single‐null shapes, the plasma density at the core–edge interface is varied from 1 × 10 19 to 8 × 10 19 m −3 to investigate the detachment plasma characteristics. The additional X‐point near the primary X‐point and target is invested in snow flake plus (SF+) and snow flake minus (SF−) configurations. Detachment at the outer target is also studied in these simulations. The degree of detachment and the radiation location are investigated using the SOLEDGE2D simulation results. It is found that advanced divertor configurations result in a deeper detachment under the same plasma density and in a reduction in the detachment threshold.